Influence of Particle Beam Irradiation on the Structure and Properties of Graphene - Wu, Xin.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This thesis focuses on the nanomanufacturing of graphene-a newly discovered, two-dimensional material with extraordinary properties-in order to realize its numerous potential applications. Combining experimental implementation with theoretical modelling, it investigates three classes of graphene nanostructure fabrication using particle beam irradiation: (i) doping of graphene using low energy nitrogen irradiation; (ii) joining of graphene sheets with laser and C, N, and Ar ion beam irradiation; and (iii) fabrication of graphene nanopores by means of focused ion beam and electron beam irradiation. The feasibility of the nanomanufacture of graphene using particle beam irradiation is demonstrated by various experimental methods, and the mechanisms involved under different types of beam irradiation are revealed using theoretical calculations. Further, the book analyzes the mechanical and electrical properties of the fabricated graphene nanostructures by means of atomic simulations to predict the application potentials of the proposed methods. The findings help promote the implementation of graphene-structure applications in industry.
Introduction -- Experiment setup and computation methods -- General mechanism during the interaction between particle beam and graphene -- Doping of graphene using low energy ion beam irradiation and its properties -- Joining of graphene by particle beam irradiation and its properties -- Fabrication of graphene nanopore by particle beam irradiation and its properties -- Conclusion.
Keywords: Optical materials; Atoms; Molecules; Microtechnology; Microelectromechanical systems; Chemistry, Physical and theoretical; Optical Materials; Atoms and molecules in external fields; Microsystems and MEMS; Theoretical Chemistry